OVERVIEW OF DIRECTION CONTROL VALVE WITH VARIOUS METERING NOTCHES - PRADEEP M. KULKARNI; DR. VINAYAK KALE (International Journal of Innovations in Engineering Research and Technology, 2021)
Present era provides us with high end technology but these high end technology also associated with high cost which many a times not justifiable. One such area is hydraulics systems in the machines. Many high end technologies like proportional valve and servo valves are developed which can provide the accurate controls on the processes as per the requirements. Still many machines in the industry are with conventional technologies. So there is a need for some low cost systems for specific application in the areas like injection molding and die casting. In this review literature survey is done to check the modeling of direction control valve and other hydraulic valves. Also the experimental results of various literatures are studied. The review paper outlines the theoretical background of Metering notches in the Direction control valve. Hydraulic set up outline diagram is drawn and Equipments required are listed with future scope, to analysis the effect of various metering notches with different viscosity fluids.